Effects of Lupinus angustifolius (cv. Arabella and Kalya) on the growth and serum profiles in broilers (Bangladesh Journal of Animal Science, 2018)
This work examined the effects of incorporation of exogenous enzyme preparation on growth and performance traits in broilers fed diet containing 400 g/Kg of L. angustifolius(cv. Arabella) of Europe and L. angustifolius (cv. Kalya) obtained from Australia. A maize- soy (MS) based diet served as a control diet and acted as positive, while non-protein control diet acted as a negative control (NPC) and fed ad libitum for 18 days. Growth rate, apparent digestibility of N, fat and excretion of essential minerals were assessed. In comparison to broilers fed maize-soy (MS) diet, broilers fed the L. angustifolius  of European origin (EL) diet, consumed less feed, had considerably lower body weight gain, as well as lower apparent digestibility. Addition of Rena phytase to the EL (ELPH) and L. angustifolius of Australian origin (ALPH) increased feed intake, however, the feed gain ratio was found to be decreased. . This study indicates that a diet containing high level of lupin meal is detrimental to feed intake broilers and thus affected their performance. However, when lupin meal diet was supplemented with Rena phytase, performance parameters were not different from those obtained from raw meal. The inclusion of lupin meal with or without exogenous enzyme had significant effect on the mineral content of the faeces and on mineral balance. The results suggest that lupin protrein is involved in the elevated loss of minerals associated with long-term effects of this seed as protein source in poultry. Compared to those of control, the N excretion was in the range of 14.9% (EL), 15.6% (ELPH) and 13.9% (ALPH). On the other hand, digestibility was found to be in the range of 78% (EL) and 73% (ELPH) than the corresponding control fed on (MS) diet. The fat excretion was found to be highest in (ALPH) fed diet 19.1% as compared to those of control. True fat digestibility was found to be at the lowest level n ALPH group. The present work has revealed a very remarkable property of L. angustifolius of Australian lupin, that has caused high level of fat excretion in the droppings of broilers fed this as compared to those of its European counterpart. It is highly likely that Australian lupin due to its gel forming character may have caused this kind of response in fecal lipid excretion.Bang. J. Anim. Sci. 2017. 46 (4): 266-272